Residual Inflammatory Risk Predicts Poor Prognosis in Acute Ischemic Stroke or Transient Ischemic Attack Patients. Issue 9 (20th July 2021) - Li, Jiejie; Pan, Yuesong; Xu, Jie; Li, Shiyu; Wang, Mengxing; Quan, Kehua; Meng, Xia; Li, Hao; Lin, Jinxi; Wang, Yilong; Zhao, Xingquan; Liu, Liping; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: It is still unclear whether the residual cholesterol and inflammatory risk in the acute phase is associated with prognosis of stroke. We aimed to investigate the proportion and relative contribution of residual cholesterol and inflammatory risk, determined by baseline low-density lipoprotein cholesterol (LDL-C) and high-sensitivity C-reactive protein (hsCRP) levels, to the risk of recurrent stroke and poor functional outcome at 1 year. Methods: In this prospective multicenter cohort study, 10 499 consecutive acute ischemic stroke and transient ischemic attack patients with levels of LDL-C and hsCRP were enrolled. Patients were divided into 4 groups: residual cholesterol risk only (LDL-C ≥2.6 mmol/L and hsCRP <3 mg/L), residual inflammatory risk (RIR) only (LDL-C <2.6 mmol/L and hsCRP ≥3 mg/L), both risk (LDL-C ≥2.6 mmol/L and hsCRP ≥3 mg/L), and neither risk (LDL-C <2.6 mmol/L and hsCRP <3 mg/L). The primary outcomes consisted of stroke recurrence and a modified Rankin Scale score of 2 to 6 within 1 year. Results: The relative proportions of patients with RIR only, residual cholesterol risk only, both risk, and neither were 21.3%, 23.7%, 14.4%, and 40.6%, respectively. RIR only was independently associated with recurrent stroke (adjusted hazard ratio, 1.18 [95% CI, 1.00–1.40]; P =0.05). The association was slightly attenuated after further adjusting for usage of antiplatelet agent and statin during 1-year follow-up in addition to the traditional risk factors (hazard ratio, 1.31 [95% CI, 0.99–1.76]; P =0.07). When applying the LDL-C cutoff value of 1.8 mmol/L in the sensitivity analyses, such association in large-artery atherosclerosis subtype was more significant (adjusted hazard ratio, 1.69 [95% CI, 1.06–2.67]; P =0.03). Patients with RIR only also had increased risk of poor functional outcome (adjusted odds ratio, 1.43 [95% CI, 1.24–1.64]; P <0.0001). Conclusions: In the patients with acute ischemic stroke or transient ischemic attack, RIR only could be predictive for recurrent stroke, especially for those with large-artery atherosclerosis, and poor functional outcome.